This AUREY BOMB (INOVASI SABUN MANDI KOMBINASI Hylocereus polyrhizus dan Lavandula angustifolia SEBAGAI ANTIOKSIDAN dan MERELAXKAN TUBUH) - Syarifah Roihanah .; Nesya Cantika Putri; Askya Falabiba; Meytha Putri Prehandhini (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2026)
This study aims to develop a bath bomb formulation based on red dragon fruit peel (Hylocereus polyrhizus) as an innovation in natural, eco-friendly body care products. Dragon fruit peel was chosen because it contains bioactive compounds such as vitamin C, flavonoids, and betalains, which have potential as antioxidants and natural colorants. This research used an experimental method with variations in extract concentration and evaluation of the physical characteristics of the product, including organoleptic test, pH, effervescent time, foam height, and specific gravity. The results showed that bath bombs containing dragon fruit peel extract had good physical characteristics: solid, stable, easily soluble (<5 minutes), and pH within a safe range (6–7.5). Additionally, variations in fragrance concentration affected aroma acceptance, with moderate concentrations producing the most balanced and preferred scent. These findings indicate that dragon fruit peel can be utilized as a natural active ingredient in bath bomb formulations to create value-added, sustainable, and eco-friendly body care products.